Profesionalisme Apoteker dalam Perspektif Nilai Obat sebagai Amanah pada Teori Konstitusi Kesehatan Nusantara - Melsi Emilia (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2025)
Pharmacist professionalism is a key component in ensuring the quality of pharmaceutical services, encompassing not only compliance with technical and scientific standards but also a deep commitment to moral and ethical principles. In the Indonesian cultural context, the concept of "medicine as a trust" (obat sebagai amanah) reflects a profound sense of responsibility, where medicine is viewed not merely as a commodity, but as a mandate that must be preserved with integrity and accountability in health care practices. This article conceptually explores the relationship between pharmacist professionalism and the moral value of trust within the framework of the Nusantara constitutional theory. This theory emphasizes the integration of legal, cultural, and moral dimensions in shaping professional conduct in Indonesia. Using a descriptive-critical approach through literature review, this study investigates how trust functions as both a legal expectation and a cultural imperative in the practice of pharmacy. The findings highlight that trust must be internalized as a core value in pharmaceutical services—manifested through ethical decision-making, transparency in drug management, and a commitment to prioritizing patient welfare. Pharmacists are not only required to uphold professional standards, but also to carry out their duties as custodians of public trust. To realize this vision, the integration of the value of trust into pharmacy education, legal regulations, and clinical practice is essential. Educational institutions, professional organizations, and regulatory bodies must work collaboratively to instill this value as part of a pharmacist’s identity. In doing so, the profession can contribute more effectively to building a health care system that is just, culturally grounded, and centered on the well-being of the people.